HUBUNGAN PERSEPSI PASIEN KONTROL TERHADAP KUALITAS LAYANAN PENDAFTARAN MELALUI SMS GATEWAY DI PUSAT MATA NASIONAL RUMAH SAKIT MATA CICENDO BANDUNG 2019 - Laili, Ayu; Sari, Rias Puspita; -, Suhat (JURNAL KESEHATAN KARTIKA, 2021)
The development of services in the hospital followed by their public demands for service quality, including the use of technology weapons. National Eye Center Eye Hospital Cicendo Bandung has implemented control patient registration service via SMS gateway. This study aims to determine the relationship of the patient perception of control over the quality of service registration via SMS gateway. The research method uses quantitative methods with a cross-sectional study design. The sampling technique accidental sampling with a total sample of 96 respondents. Data was collected by questionnaire. Analysis of the data in two ways, namely univariate and bivariate, the test used is chi-square with significance level p value = 0.05. Results of the analysis showed that out of 96 respondents 50 (52.1%) of respondents have a perception of the quality of service is poor. The analysis showed no relationship between hope (p value = 0, 012) with control patients' perceptions of service quality through registration SMS gateway. National Eye Center Eye Hospital Cicendo Bandung Hospital is expected to improve services related to patient waiting time and conduct regular surveys related to SMS gateway service